Is Kidney Injury Molecule 1 a Valuable Tool for the Early Diagnosis of Contrast-Induced Nephropathy?. Issue 8 (December 2015) - Akdeniz, Derya; Celik, Huseyin Tugrul; Kazanci, Fatmanur; Yilmaz, Hakki; Yalcin, Serkan; Bilgic, Mukadder Ayse; Ruzgaresen, Nuket; Akcay, Ali; Eryonucu, Beyhan
Abstract : Aim/Scope: Contrast-induced nephropathy (CIN) is a common complication of diagnostic/therapeutic procedures. Serum creatinine levels are sensitive but often lead to diagnostic delays in acute kidney injury and potential misclassification of actual injury status. Kidney injury molecule (KIM-1) is a novel early marker of acute kidney injury. The aim of our study was to evaluate the KIM-1 levels in patients with CIN. We performed a single-center, nested case-control study. Materials and Methods: Three thousand two hundred patients who had undergone coronary angiography were included in the study. Thirty-two patients were diagnosed with CIN. Twenty patients who had undergone coronary angiography but did not have CIN were evaluated as a control group (n = 20). The diagnosis of CIN was performed according to the KDIGO 2012 Acute Kidney Injury Guideline criteria. Urinary KIM-1 levels were measured by enzyme-linked immunosorbent assay before as well as on the 6th and 48th hours of contrast exposure. Serum creatinine levels were measured before as well as on the 24th and 48th hours after angiographic procedure. Results: We demonstrated that KIM-1 levels increased in the patients with CIN significantly on the sixth hour when compared with the baseline ( P < 0.01; median levels, 0.27 and 0.70 mg/dL) but not in the controls ( P = 0.107). The precontrast and 48th-hour KIM-1 levels were median ones and were also significantly different ( P = 0.001, the median levels were 0.27 and 0.60 mg/dL, respectively). Conclusions: Because creatinine is a sensitive but a late marker of CIN, KIM-1 may be used for early diagnosis and early initiation of treatment and may reduce risk for morbidity.